Comparative analysis of different methods for evaluating quality of Quercus ilex seedlings inoculated with Tuber melanosporum - Andres-Alpuente, Antonio; Sanchez, Sergio; Martin, Maria; Javier Aguirre, Angel; Barriuso, Juan J. (MYCORRHIZA, 2014)
The quality of seedlings colonized by Tuber melanosporum is one of the main factors that contributes to the success or failure of a truffle crop. Truffle cultivation has quickly grown in European countries and elsewhere, so a commonly shared seedling evaluation method is needed. Five evaluation methods are currently published in the literature: three are used in Spain and two in France and Italy. Although all estimate the percentage colonization by T. melanosporum mycorrhizae, they do it in different ways. Two methods also estimate total number of mycorrhizae per seedling. Most are destructive. In this work, ten batches of holm oak seedlings inoculated with T. melanosporum from two different nurseries were evaluated by means of the five methods noted above. Some similarity was detected between the percentages of T. melanosporum mycorrhizae estimated by each method but not in their ability to assess the suitability of each batch. We discuss the advantages and disadvantages for each method and suggest approaches to reach consensus within the truffle culture industry for certifying mycorrhizal colonization by T. melanosporum and seedling quality.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Black truffle; Certification; Holm oak; Mycorrhization; Nurseries; Truffle culture

A quantitative and molecular examination of Tuber melanosporum mycorrhizae in Quercus ilex seedlings from different suppliers in Spain - Alvarado, P.; Manjon, J. L. (FOREST SYSTEMS, 2013)
Aim of study: The aim of the work was to determine the degree of mycorrhization of Quercus ilex L. subsp. ballota (Desf.) Samp. by the black truffle fungus T. melanosporum Vittad. by quantitative and molecular analyses. Area of study: seedlings inoculated by different Spanish suppliers. Material and methods: The internal transcribed spacers (ITS) of mycorrhizae from different plants were amplified by nested PCR involving fluorescently-labelled primers, and the amplicons either directly sized by ARISA or analysed by TRFLP following their digestion with restriction endonucleases. TRFLP analysis distinguished between mycorrhizae of T melanosporum, T. indicum Cooke & Massee and T. borchii Vittad., as suggested possible by virtual (in silico) TRFLP analysis and real TRFLP analysis of the ascomata of these species. Main results: Significant differences between suppliers were detected in terms of the mean number of mycorrhizae established per plant and percentage mycorrhization. These results allowed the following quality standards for 2 year-old plants to be proposed: a) good quality: >3,000 mycorrhizae/plant, >40% mycorrhization, b) medium (acceptable): >3,000 mycorrhizae/plant, >30% mycorrhization, c) low quality: <3,000 mycorrhizae/plant or <30% mycorrhization, always supposing the mycorrhizae counted represent the species of interest as confirmed by the presence of its DNA and the absence of DNA belonging to contaminating species. Finally, a new microsatellite allelic map obtained from the analysis of several T melanosporum populations across Spain was used to provide a tool capable of determining the geographic origin of the fungi used to inoculate plants. Research highlights: The proposed quality standards can be useful for the evaluation and certification of commercialized Q. ilex plants mycorrhized with T. melanosporum.
The following values have no corresponding Zotero field: pub-location: CTRA CORUNA KM 7 5, MADRID, 28040, SPAIN publisher: INST NACIONAL INVESTIGACION TECHNOLOGIA AGRARIA ALIMENTARIA
Keywords: Certification; fungi; mycorrhiza; TRFLP; truffle